2020
DOI: 10.1007/s13300-020-00839-5
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Effectiveness of Dulaglutide in Patients with Type 2 Diabetes Mellitus: A Literature Review

Abstract: Introduction: Randomized controlled trials (RCTs) have demonstrated the efficacy of dulaglutide in adults with type 2 diabetes mellitus (T2DM), but results may not be generalizable in routine practice. This pragmatic literature review aimed to summarize real-world evidence (RWE) for dulaglutide. Methods: The MEDLINE, EMBASE, NHS Economic Evaluation Database, and Health Technology Assessment databases were searched from January 2014 to July 2019 for studies providing RWE for dulaglutide in adults with T2DM rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
18
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 35 publications
5
18
0
1
Order By: Relevance
“…In the AWARD-3 trial, although there was no difference in the overall degree of treatment satisfaction between the dulaglutide and metformin arm, a significantly greater reduction in the perceived frequency of hyperglycemia was observed in the dulaglutide arm at 52 weeks [11]. An observational study showed greater adherence to and persistence with dulaglutide treatment as compared to twicedaily or weekly exenatide, lixisenatide, or liraglutide treatment [12]. Similar results were reported from comparisons with semaglutide and weekly exenatide [13].…”
Section: Introductionsupporting
confidence: 58%
“…In the AWARD-3 trial, although there was no difference in the overall degree of treatment satisfaction between the dulaglutide and metformin arm, a significantly greater reduction in the perceived frequency of hyperglycemia was observed in the dulaglutide arm at 52 weeks [11]. An observational study showed greater adherence to and persistence with dulaglutide treatment as compared to twicedaily or weekly exenatide, lixisenatide, or liraglutide treatment [12]. Similar results were reported from comparisons with semaglutide and weekly exenatide [13].…”
Section: Introductionsupporting
confidence: 58%
“…In addition, it is limited by the fact that HbA 1c levels were not concealed and investigators used a variety of different glucoselowering agents (other than GLP-1 receptor agonists) to control HbA 1c levels according to their best judgment and not according to a protocol-defined target. In the REWIND study, treatment adherence to dulaglutide exceeded that of real-world observations, although real-world studies on adherence to dulaglutide had shorter follow-ups (25,26). Drop-in antihyperglycemic therapies clearly could have had an effect on the change in HbA 1c from baseline, but the reverse may also be true, as change in HbA 1c could have an effect on the introduction of drop-in therapies at different time points in both treatment groups; therefore, an analysis on the impact of drop-in therapies on the change in HbA 1c is not presented as there is no clear assignment of response and predictor variables in this case.…”
Section: Discussionmentioning
confidence: 87%
“…Guidelines also recommend that HbA 1c goals are individualized on the basis of patient characteristics, patient preferences and goals, and risk of treatment-related adverse effects such as hypoglycemia and weight gain [ 1 , 2 ]. Previous real-world studies have focused on the prevalence of adults with type 2 diabetes mellitus achieving an HbA 1c goal of < 7.0% despite the recommended individualization of glycemic goals [ 9 14 ].…”
Section: Introductionmentioning
confidence: 99%